Prevalence of Hepatitis B and C in Urban Patients Undergoing Cataract Surgery - Arshad Shaikh, Waqar ul Huda, Naz Jameel, Uzma Fasih, Attiya Rehman (Pakistan Journal of Ophthalmology, 2018)
Purpose: This study was carried out to measure the prevalence of HBV and HCV in cataract surgical patients. Material and Methods: This was a prospective observational study conducted at ophthalmology department Abbasi shaheed hospital Karachi from December 2010 to April 2011. A total of 150 patients above the age of 30 years undergoing elective cataract surgery were screened for hepatitis B and C. The patients were screened for HBs Ag and Anti-HCV using immunochromatography (ICT method). Those who were positive by ICT were further tested by Enzyme Linked Immunosorbent Assay (ELISA). Results: HBV or HCV was present in 26 (17.33%) patients out of 150. Prevalence among the male patients was 20% while among female was 13.33%. Out of 26 positive patients, 7 patients (26.92%) were hepatitis B positive and 19 patients (73.07%) were hepatitis C positive. Conclusion: It is mandatory to be screened for hepatitis B and C preoperatively for every patient undergoing cataract surgery.